Study of new modulation strategies for neutral point clamped multi-level inverter - Bhaskar Mahadevan (2019)
Multi-level Inverters convert a fixed DC input to a nearly sinusoidal AC output. Both the output amplitude and frequency may be controlled. Inverters find applications in domestic uninterrupted supplies, grid connected sources, power quality devices, variable speed drives, etc. Several modulation techniques have been implemented for generation of gate pulses and control of inverter output. Recent development in Neutral Point Clamped (NPC) multi-level inverters have increased their application in machine drives. A novel modulation strategy named, Hexagon Shift Space Vector Modulation (HSSVM), for NPC MLI is presented. This strategy aims at reducing the torque ripples during transience and improves steady state characteristics of the drive system. The IPMSM motor is chosen as the load to be fed by the NPC MLI controlled by the proposed strategy. The forward and reverse motoring of the MLI-Motor system is simulated in MATLAB Simulink and the analysis of the performance is presented.